Deception under Time Pressure: Conscious Decision or a Problem of Awareness? - Kai Konrad; Tim Lohse; Sven Simon (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We conduct a laboratory experiment of self-serving deceptive behavior and exogenously vary the level of reflection time. We find that time pressure leads to more honesty compared to sufficient contemplation time. Moreover, more reflection time increases awareness of the misreporting opportunity. However, it has no effect on the conscious decision of whether to misreport or not. Due to subjects' lack of awareness under time pressure we conclude that misreporting is not the intuitive response.
Keywords: C91; D83; K42; 330